2021
DOI: 10.1017/s1047951121003115
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, liver-related biomarkers, and distribution of fat and lean mass in young patients with Fontan circulation

Abstract: Introduction/aim: Young patients with Fontan circulation may have low serum 25-hydroxyvitamin D levels, an affected liver, and unhealthy body compositions. This study aimed to explore the association between vitamin D intake/levels, liver biomarkers, and body composition in young Fontan patients. Method: We collected prospective data in 2017 to 2018, obtained with food-frequency questionnaires, biochemical analyses of liver biomarkers, and dual-energy X-ray absorptiometry scans in 44 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…23,50 Fontan-associated myopenia While reductions in skeletal muscle (also known as fat-free mass) are prevalent in those with complex CHD, limited data have suggested that the deficiencies are more pronounced in the setting of a Fontan circulation, particularly in the lower half of the body. 8,9,39,[51][52][53] A study by Powell and colleagues observed a 14% increase in adiposity and a 15% decrease in lean muscle mass in adolescents with a Fontan circulation when compared to those with complex CHD. 20 In the setting of Fontan physiology, this is especially concerning because the skeletal muscle in the lower limbs acts as a peripheral muscle pump contributing to venous return and cardiac filling.…”
Section: Abnormal Body Compositionmentioning
confidence: 99%
See 4 more Smart Citations
“…23,50 Fontan-associated myopenia While reductions in skeletal muscle (also known as fat-free mass) are prevalent in those with complex CHD, limited data have suggested that the deficiencies are more pronounced in the setting of a Fontan circulation, particularly in the lower half of the body. 8,9,39,[51][52][53] A study by Powell and colleagues observed a 14% increase in adiposity and a 15% decrease in lean muscle mass in adolescents with a Fontan circulation when compared to those with complex CHD. 20 In the setting of Fontan physiology, this is especially concerning because the skeletal muscle in the lower limbs acts as a peripheral muscle pump contributing to venous return and cardiac filling.…”
Section: Abnormal Body Compositionmentioning
confidence: 99%
“…48 Concerningly, adiposity tends to accumulate in the trunk or abdominal area. 9,53,70 Given this distribution tendency, there may be merit in measuring waist circumference across all ages to aid in monitoring for excess adiposity although this measurement will be confounded in the presence of ascites. 23,50,[70][71][72] Ascites is likely to develop in 17% of those with a Fontan circulation as a subsequent complication of Fontan-associated liver disease.…”
Section: Increased Adipositymentioning
confidence: 99%
See 3 more Smart Citations